Enhanced accumulation of N-terminally truncated Aβ with and without pyroglutamate-11 modification in parvalbumin-expressing GABAergic neurons in idiopathic and dup15q11.2-q13 autism - Frackowiak, Janusz (Acta Neuropathol Commun, 2020)
Autism, the most frequent neurodevelopmental disorder of a very complex etiopathology, is associated with dysregulation of cellular homeostatic mechanisms, including processing of amyloid-β precursor protein (APP). Products of APP processing — N-terminally truncated amyloid-β peptide (N-tr-Aβ) species — are accumulated in autism in neurons and glia in the cortex, cerebellum, and subcortical structures of the brain. This process in neurons is correlated with increased oxidative stress. Because abnormally high levels of N-tr-Aβ are detected in only a fraction of neurons in the prefrontal cortex, we applied immunocytochemical staining and confocal microscopy in autopsy brain material from idiopathic and chromosome 15q11.2-q13 duplication (dup-15) autism to measure the load of N-tr-Aβ in the cells and synapses and to identify the subpopulation of neurons affected by these pathophysiological processes. The peptides accumulated in autism are N-terminally truncated; therefore, we produced a new antibody against Aβ truncated at N-terminal amino acid 11 modified to pyroglutamate to evaluate the presence and distribution of this peptide species in autism. We also quantified and characterized the oligomerization patterns of the Aβ-immunoreactive peptides in autism and control frozen brain samples. We provide morphological evidence, that in idiopathic and dup-15 autism, accumulation of N-tr-Aβ with and without pyroglutamate-11 modified N-terminus affects mainly the parvalbumin-expressing subpopulation of GABAergic neurons. N-tr-Aβ peptides are accumulated in neurons’ cytoplasm and nucleus as well as in GABAergic synapses. Aβ peptides with both C-terminus 40 and 42 were detected by immunoblotting in frozen cortex samples, in the form of dimers and complexes of the molecular sizes of 18-24kD and 32-34kD. We propose that deposition of N-tr-Aβ specifically affects the functions of the parvalbumin-expressing GABAergic neurons and results in a dysregulation of brain excitatory–inhibitory homeostasis in autism. This process may be the target of new therapies.